Integrating the circular economy into engineering programs in India: A study of students' familiarity with the concept. Issue 3 (June 2021) - Venugopal, Pingali; Kour, Harwinder
Human production and consumption activities are depleting the earth's resources faster than they are being replenished. The Global Footprint network estimates "Earth Overshoot Day 2020" (the day the use of natural resources during the year crosses the regeneration capacity for the year) to be 22 August. A shift from linear to circular economy (CE) practices offers an alternative approach that favors environmental conservation, integrating economic growth with environmental protection. While it is important to educate engineering students about sustainable models, environmental education is mandatory in India and a 6-month module introduces various concepts in all university programs. This article examines the extent of familiarity of Indian engineering students with the concept of a circular economy. A two-phase methodology was used, with 148 students of a National Institute of Technology participating in the study. In Phase 1, which focused on the students' awareness of the CE, it was found that only a third were familiar with the concept. In Phase 2 the students, after having had the concept explained to them, identified possible barriers to incorporating it into the syllabus. The implications of integrating the concept with the syllabus are discussed.